Ekonomiese groei versus herverdeling as metodes om armoede in Suid-Afrika te verlig - Merwe, S. J. van der (Koers, 1997)
Economic growth versus redistribution as methods to relieve poverty in South AfricaThe most significant economic problems in South Africa are unemployment, concomitant with widespread poverty and an unequal distribution of income. One of the major mechanisms reducing poverty and inequality is the creation of employment opportunities resulting from economic growth. The sources of economic growth are capital accumulation (including all new investments in land, physical equipment and human resources), growth in the labour force, and technological progress. This article focuses on the issue of growth versus distribution. Job creation is investigated in terms of two paradigms, namely redistribution-through-growth (as associated with the NEM) and the growth-through-redistribution (as associated with the RDP). It is concluded that neither economic growth (as supported by the NEM) nor redistribution in itself (as supported by the RDP) is sufficient for job creation. An alternative or integrated approach, namely redistribution and growth, is recommended for South Africa.